2019
DOI: 10.1073/pnas.1908576116
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic, epigenetic, and functional analyses implicate neutrophil diversity in the pathogenesis of systemic lupus erythematosus

Abstract: Neutrophil dysregulation is implicated in the pathogenesis of systemic lupus erythematosus (SLE). SLE is characterized by elevated levels of a pathogenic neutrophil subset known as low-density granulocytes (LDGs). The origin and phenotypic, functional, and pathogenic heterogeneity of LDGs remain to be systematically determined. Transcriptomics and epigenetic assessment of lupus LDGs, autologous normal-density neutrophils, and healthy control neutrophils was performed by bulk and single-cell RNA sequencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(200 citation statements)
references
References 45 publications
9
189
1
1
Order By: Relevance
“…Analysis of recently published human BM neutrophil gene expression data ( 37 ) also showed higher levels of expression for a number of antioxidant enzymes, such as GPX1,3,4 ; SOD2 ; HMOX2 ; TXNRD1 ; and SRXN1 in segmented mature neutrophils ( Supplemental Figure 6A ). A close look into the transcriptome of enriched CD10 + and CD10 – LDNs from SLE patients published by Mistry et al, revealed a highly similar pattern of increased expression of SOD2 , HMOX2 , SRXN1 , and TXNRD1 in mature CD10 + LDNs ( 38 ) ( Supplemental Figure 6, B and C ).…”
Section: Resultsmentioning
confidence: 70%
“…Analysis of recently published human BM neutrophil gene expression data ( 37 ) also showed higher levels of expression for a number of antioxidant enzymes, such as GPX1,3,4 ; SOD2 ; HMOX2 ; TXNRD1 ; and SRXN1 in segmented mature neutrophils ( Supplemental Figure 6A ). A close look into the transcriptome of enriched CD10 + and CD10 – LDNs from SLE patients published by Mistry et al, revealed a highly similar pattern of increased expression of SOD2 , HMOX2 , SRXN1 , and TXNRD1 in mature CD10 + LDNs ( 38 ) ( Supplemental Figure 6, B and C ).…”
Section: Resultsmentioning
confidence: 70%
“…Moreover, the underlying differences in lupus skin, such as enhanced IFN-I signaling 7,112,113 and defects in protective Langerhans cell population 114 could inform the extent and nature of neutrophil-mediated systemic responses. The exact mechanism might in addition be influenced by the neutrophil/LDG phenotype, as heterogeneity within these populations has become more apparent in SLE 65 . Our findings of elevated CXCR4 and ICAM1 hi CXCR1 lo (rTM) circulating populations, particularly in SLE LDGs, further add to this heterogeneity and suggest that some of the more pro-inflammatory granulocytes in blood might have prior "tissueexperience", i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While both the aged (CXCR4 hi ) and the reverse migrating (ICAM1 hi CXCR1 lo ) neutrophil phenotypes have been associated with inflammatory functions and tissue injury in different murine models 51,52,60 , few studies have been performed on these cell populations in human disease. Given the emerging role of neutrophils in SLE 11,[15][16][17] and their apparent heterogeneity 18 , we investigated whether PMNs or low density granulocytes (LDGs) 64,65 from SLE patients demonstrated the phenotypes of aged, CXCR4 hi , or reverse migrating, ICAM1 hi CXCR1 lo , neutrophils. Flow cytometry profiling of PMNs and LDGs revealed higher CXCR4 expression on the surface of these cells in SLE patients, compared to healthy controls ( Fig.…”
Section: Figure 4: Uvb Light-triggered Neutrophil Migration To the Kimentioning
confidence: 99%
“…SLE is characterized by neutrophil subsets known as low-density granulocytes (LDGs). When compared to other immune cell subtypes, LDGs showed the highest expression of interferon gamma genes, CD10 with subpopulations that were speci cally positive correlation with disease severity and coronary patterns 44 .. In addition, neutrophils patterns were also described in the emerging COVID-19 infectious disease.…”
Section: Anticipated Resultsmentioning
confidence: 90%